COMMUNITY DEVELOPMENT MASYARAKAT BERBASIS KULIAH KERJA NYATA TEMATIK POSDAYA MASJID - Miftahus Salam; Nadiah Citra Amania Sulfa (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
The general purpose of the Mosque-Based Posdaya Thematic KKN especially for students, is to help students improve their ability to learn together with the community, apply religious knowledge in integration with technology, arts and culture that have been studied directly and see whether the application process is in accordance with the theory obtained during college, and bring benefits to society. The results of the activity stated that the Thematic Posdaya KKN based on the STAI At-Taqwa Bondowoso Mosque included, among others, at the KKN location, the mosque which was the center of activity had advantages and potential in the fields of religion, education, health, and also the economy. Where in the religious field it is shown by several existing activities such as reading sholawat nariyah, khatmil Qur'an, Istighosah, Practice of Tajhizul Mayyit, and praying Fatayat. In education, there are TPQ and madrasah diniyah which are taught by residents around the mosque. In the health sector, there are toddler and elderly posyandu whose implementation stage is often announced through mosque speakers. And with entrepreneurship, communication about business activities is starting to be discussed by teenagers and people remember that after praying in congregation they sit on the porch while talking. Where the form of a new product initiated by students and the public is SUREN drink (duren milk).